The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/srep16603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-morbidities on the development of oral feeding ability in pre-term infants: a retrospective study

Abstract: Pre-term infants frequently experience difficulties in attaining independent oral feeding, thus delaying the achievement of an adequate nutritional status and hospital discharge. The aim of this retrospective, single-centre, observational study was to investigate the effect of co-morbidities on the timing of the achievement of full oral feeding in pre-term infants. The neonatal and feeding data of 84 infants born at a gestational age of <32 weeks were collected, and the effect of co-morbidities on the achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 41 publications
3
33
0
2
Order By: Relevance
“…In this sample, many participants presented with medical risk factors which previous research has associated with feeding difficulties, such as RDS. 19,[30][31][32][33] For example, the results of the present study appear to support that RDS may impact on breastfeeding. Although these results should be interpreted with caution due to a lack of statistical significance, Table 4 indicates that a larger percentage of participants without RDS exhibited mature breastfeeding characteristics, than the percentage of participants with RDS, except for latching duration.…”
Section: Resultssupporting
confidence: 62%
“…In this sample, many participants presented with medical risk factors which previous research has associated with feeding difficulties, such as RDS. 19,[30][31][32][33] For example, the results of the present study appear to support that RDS may impact on breastfeeding. Although these results should be interpreted with caution due to a lack of statistical significance, Table 4 indicates that a larger percentage of participants without RDS exhibited mature breastfeeding characteristics, than the percentage of participants with RDS, except for latching duration.…”
Section: Resultssupporting
confidence: 62%
“…In our study, we reported the earliest initiation of oral feeding at 31 +5 weeks PMA (compared to a previous report of 33 +1 weeks), which indicates that developing the early initiation of oral feeding is possible (Jackson et al., ). The reason for the discrepancy with these findings may be due to the wider range of GA of infants in this study, which is from 25 +1 to 36 +6 weeks, or due to other confounding factors associated with time to achieve oral feeding with breast milk, such as LBW, GA and SGA (Gianni et al., ). In addition, neonatal Cochrane reviews have identified numerous studies regarding the use of non‐nutritive sucking or oral stimulation and concluded that these practices do aid in the transition from gavage to oral feeding (Foster, Psaila, & Patterson, ; Greene, O'Donnell, & Walshe, ).…”
Section: Discussionmentioning
confidence: 55%
“…17,18 In addition to the physiological immaturity, development of oral feeding skill and endurance in premature infants is further impacted by the multiple comorbidities that they develop during the NICU stay. 5,6 AOP is often attributed for impaired feeding and weight gain in premature infants because of limited tissue oxygen delivery to aerodigestive structures during feeding. 11,19,20 The impact of AOP in individual infant oral feeding physiology is not well described, but it is plausible that underlying anemia, especially if uncompensated, may affect feeding endurance and proficiency.…”
Section: Discussionmentioning
confidence: 99%